1993
DOI: 10.1038/jcbfm.1993.61
|View full text |Cite
|
Sign up to set email alerts
|

Defective Brain Energy Metabolism Shown by in vivo31P MR Spectroscopy in 28 Patients with Mitochondrial Cytopathies

Abstract: Summary:We studied brain energy metabolism by phos phorus magnetic resonance spectroscopy e1p MRS) in 28 patients with mitochondrial cytopathies, and 20 normal control subjects. Fourteen patients had myopathy alone, six had only mild brain symptoms, and eight showed dif ferent degrees of brain involvement. Brain 31p MRS showed a low phosphocreatine content in all patients, accompanied by a high inorganic phosphate in 14 of 28 patients. The average value of the Pi concentration in the patient group was signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 28 publications
7
53
1
Order By: Relevance
“…Indeed, a similar cerebral 31 P-MRS pattern has been observed in some mitochondrial cytopathies (21,22). However, a consistent pattern of mitochondrial abnormalities (e.g.…”
supporting
confidence: 66%
“…Indeed, a similar cerebral 31 P-MRS pattern has been observed in some mitochondrial cytopathies (21,22). However, a consistent pattern of mitochondrial abnormalities (e.g.…”
supporting
confidence: 66%
“…At present, the recorded volume is large and there are no clear differentiations between rest and active states. Low brain PCr values were found in patiens with MELAS, Leigh disease, PEO and Leber's hereditary optic atrophy [26][27][28][29], but results were less consistent in myoclonic epilepsy with ragged-red fibers (MERRF) [27,30]. The specificity and sensitivity of these findings remain to be determined and further technological development is necessary before brain 31 P MRS becomes a useful method for functional evaluation.…”
Section: Brainmentioning
confidence: 96%
“…72,73 Persistently low brain PCr values have been found in patients with a number of mitochondrial disorders, including mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS), Leigh's disease, progressive external opthalmoplegia (PEO), and Leber's hereditary optic atropy. 74,75 Reduced PCr concentrations have also been reported in migraine, which has been postulated to be associated with abnormal mitochondrial function. 76,77 Several 31 P MRS studies have suggested a connection between decreased levels of PCr and bipolar disorder (Table 5).…”
Section: Elevated Lactate In Bipolar Disordermentioning
confidence: 99%